2022
DOI: 10.3399/bjgp.2022.0350
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the integration of primary care in pandemic response plans: a qualitative interview study of Canadian family physicians

Abstract: Background: As the first point of contact in healthcare, primary care providers play an integral role in pandemic response. Despite this, primary care has been overlooked in previous pandemic plans, with a lack of emphasis on ways in which the unique characteristics of family practice could be leveraged to create a more effective response. Aim: To explore family physicians’ perceptions of the integration of primary care in the COVID19 pandemic response. Design and Setting: Descriptive qualitative approach exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…During COVID-19, PPE held deep symbolic meaning for FPs, representing the health system's lack of respect for primary care. The lack of priority placed on primary care in pandemic responses, including in the planning for PPE, has been reported in other highincome countries [38][39][40][41]. The limited representation of primary care leaders in pandemic response decisionmaking bodies [9,42] contributed to hospital-centric PPE plans, and under-appreciated both the potential risk of COVID-19 to primary care providers [43], as well as the contribution of primary care in alleviating demand for hospital-based services [16].…”
Section: Discussionmentioning
confidence: 99%
“…During COVID-19, PPE held deep symbolic meaning for FPs, representing the health system's lack of respect for primary care. The lack of priority placed on primary care in pandemic responses, including in the planning for PPE, has been reported in other highincome countries [38][39][40][41]. The limited representation of primary care leaders in pandemic response decisionmaking bodies [9,42] contributed to hospital-centric PPE plans, and under-appreciated both the potential risk of COVID-19 to primary care providers [43], as well as the contribution of primary care in alleviating demand for hospital-based services [16].…”
Section: Discussionmentioning
confidence: 99%
“…The provision of virtual care became an expected role for FPs during the COVID-19 pandemic [54] and is part of a multi-pronged strategy to minimise exposure risks for patients, FPs, and clinic staff [55] while mitigating PPE needs associated with in-person consultations [56] during a pandemic. Future research should evaluate the effectiveness of increasing the use of virtual modalities in primary care during flu seasons and for clinically vulnerable patients to reduce infection risks.…”
Section: Discussionmentioning
confidence: 99%
“…We described practice- and system-based approaches used in four regions in Canada to mitigate the risk of COVID-19 in primary care settings. Many FPs in Canada and elsewhere felt poorly guided by public health and IPAC guidelines that largely focused on acute care settings ( Hoernke et al 2021 ; Houghton et al 2020 ; Khunti et al 2020 ; Mathews et al 2022 , 2023b ) and worked to tailor these guidelines to suit primary care settings. FPs who participated in our study demonstrated their ability to enact all five IPAC elements in their practices (see Table 1 ), despite PPE shortages.…”
Section: Discussionmentioning
confidence: 99%